Collaboration of Predisposing and Enabling Factors in Stunting Prevention in Soa-Sio Village, Tidore Islands City - Megawati Istiqamah; Sitti Nurhidayanti Ishak; Norma B. Toduho; Mayasari Soamole; Hestyn Amalia (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
Stunting is a chronic nutritional problem resulting from long-term nutrient deficiency that has a systemic impact on children’s intellectual capacity. This qualitative study aims to analyze the relationship between predisposing and enabling factors in stunting prevention efforts in Soa-Sio Village, Tidore Kepulauan City. Data were collected through in-depth interviews with seven mothers of stunted toddlers as primary informants and one program officer as a key informant, with data verification using source triangulation. The study findings indicate that prevention efforts have not been fully effective due to gaps in health literacy and household sanitation issues. Regarding predisposing factors, although 100% of respondents had been exposed to information about stunting, 71.4% understood stunting only as a condition of short stature without realizing its cognitive impacts. Meanwhile, regarding enabling factors, physical facilities and clean water are adequate, but their utilization is hindered by communication barriers stemming from health workers’ formal and inflexible approach to local languages. Significant environmental barriers were also found in the area of sanitation, where 28.5% of respondents did not have a private toilet and still practiced shared sanitation. In conclusion, the main barriers to stunting prevention stem from mothers’ low cognitive understanding and poor household sanitation, which have not kept pace with the available physical infrastructure. It is recommended that the Soa-Sio Community Health Center reorient its educational strategy by using interactive counseling methods in the local language, and that a cross-sectoral program be implemented to provide incentives for the construction of sanitary toilets.